The developmental origins of obesity - Barker, David (Henry Stewart Talks, 2007)
Associations between early growth and later disease, The supply of nutrients to a baby has important long term effects, Developmental plasticity, The Fetal Origins Hypothesis, Childhood growth, Adiposity rebound, The effects of the physical and social environments cannot be understood without knowledge of individual history, The cycle of inequality